Noninvasive quantification of granzyme B in cardiac allograft rejection using targeted ultrasound imaging - Jin, Yunjie; Gao, Peng; Liang, Lifei; Wang, Yuhang; Li, Jiawei; Wang, Jiyan; Hou, Jiangang; Yang, Cheng; Wang, Xiaolin (Frontiers in Immunology, 2023)
Objective: Endomyocardial biopsy is the gold standard method for diagnosis of cardiac allograft rejection. However, it causes damage to the heart. In this study, we developed a noninvasive method for quantification of granzyme B (GzB) in vivo by targeted ultrasound imaging, which detects and provides quantitative information for specific molecules, for acute rejection assessment in a murine cardiac transplantation model.Microbubbles bearing anti-GzB antibody (MBGzb) or isotype antibody (MBcon) were prepared. Hearts were transplanted from C57BL/6J (allogeneic) or C3H (syngeneic) donors to C3H recipients. Target ultrasound imaging was performed at Days 2 and 5 post-transplantation. A pathologic assessment was performed. The expression of granzyme B and IL-6 in the heart was detected by Western blotting.Results: After MB injection, we observed and collected data at 3 and 6 min before and after the flash pulse. Quantitative analysis revealed that the reduction in peak intensity was significantly higher in the allogeneic MBGzb group than in the allogeneic MBcon group and isogeneic MBcon group at PODs 2 and 5. In the allogeneic groups, granzyme B and IL-6 expression levels were higher than those in the isogeneic group. In addition, more CD8 T cells and neutrophils were observed in the allogeneic groups.Conclusions: Ultrasound molecular imaging of granzyme B can be used as a noninvasive method in acute rejection detection after cardiac transplantation.